RESPON PENGEMUDI OJEK KONVENSIONAL TERHADAP PENGEMUDI OJEK ONLINE DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Rida Andryati Putri; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Today's technological developments are something that cannot be avoided and have different effects on each society, such as technological developments in the transportation sector. At present the transportation sector is experiencing developments, such as in the past, people only knew to use transportation services manually but nowadays the use of transportation services can be done using internet-based applications. For example, the development of conventional ojek driver transportation services to online ojek drivers. The formulation discussed in this study is how the response of conventional ojek drivers to online ojek drivers in Mandau District, Bengkalis Regency, and what factors make conventional ojek drivers still survive in the presence of online ojek drivers. The theory used is the response theory according to Sukamto, namely there are three cognitive, affective, and conative. Data analysis used descriptive method with a quantitative approach. The data collection technique in this study was nonprobability sampling with a census method with a total of 97 respondents. From the results of research in the field it can be concluded that the response of conventional motorcycle taxi drivers to online motorcycle taxi drivers in Mandau District is positive with sufficient cognitive response, affective response affects, and low conative response. Meanwhile, there are two factors that influence conventional motorcycle taxi drivers, namely internal factors and external factors. Internal factors are factors that exist from within and external factors are factors that exist from outside that influence conventional motorcycle taxi drivers to survive.Keywords: Response, conventional motorcycle taxi drivers